The effect of salinity on chlorophyll, proline and mineral nutrients in common weeds of coastal rice fields in Malaysia - Md. Abdul Hakim,; Juraimi, Abdul Shukor; Musa, Mohamed Hanafi; Ismail, Mohd Razi; Yusop, Mohd Rafii; Aslani, Fazad; Selamat, Ahmad (Triveni Enterprises, 2014)
Six weed species? (Leptochola chinensis, Echinochloa crus-galli, Echinochloa colona, Jussiaea linifolia, Oryza sativa (weedy rice) and Cyperus iria) were tested for their salt tolerant traits in terms of chlorophyll, proline and mineral nutrients accumulation against different salinity levels (0, 4, 8, 16, 24, 32, and 40 dS m-1). Chlorophyll a, b and total chlorophyll content, proline and mineral nutrients accumulation were determined. Salt stress showed prominent effect on all the parameters investigated and there were significant variations between the all weed species. Chlorophyll content, K+, Ca2+ and Mg2+ ions in both shoots and roots significantly decreased; while proline and Na+ accumulation significantly increased with increasing salinity up to 40 dS m-1. In terms of overall performance, Cyperus iria and E. crus-galli were relatively more tolerant; E. colona and J. linifolia were tolerant; L. chinensis and O. sativa L were salt sensitive, respectively.